Pengaruh Tyre Soil Terhadap Daya Dukung Pondasi Dangkal, Pada Tanah Ekspansif Padat Dengan Pembasahan Menggunakan Bentuk Permodelan Di Laboratorium - Nur Andajani, (Teknika, 2006)
One of way to prevent foundation damage of expansive soil are by repairing the expansive soil using tyre soil, because it had been proven that tyre soil can function as building strengthen structure. It is important to do a certain research to exercise the effect of tyre soil of the bearing capacity  of shallow foundation. Expectedly,  result study of the using of tyre soil can strengthen bearing capacity and  the descent of the settlement.This study will be done using model experiment in the laboratory. Sample study  is the Citraland ekspansif soil with LL = 198% and given 15% fly ash. The study will be done by condition optimum of water content ( Wopt ) from proctor standard result, then will be wetting in 3 and 5 days. Each of soil type will be given small tyre soil, large soil tyre and without tyre soil. Total sample will be tested are 6 sample, comprise of 3 samples will be wetting in 3 days and 3 samples will be wetting in 5 days.The result shows that by adding tyre soil material influence of bearing capacity foundation increase, and the of settlement may decrease. For the experiment sample wetting for 3 days, treated the bearing capacity increase as 30 % for the sample added by small tyre soil and the sample added by large tyre soil will increase as 56.67 %. For the experiment sample wetting for 5 days,  the bearing capacity will increase as 33.33 % for sample by small tyre soil, and   added by larger tyre soil will increase as 56.86 %.